European Union: Shadow WTO agricultural domestic support notifications - Josling, Timothy Edward; Swinbank, Alan (International Food Policy Research Institute, 2008)
The notification of the level of domestic support to the World Trade Organization (WTO) is intended to reflect compliance with obligations entered into at the time of the Uruguay Round. WTO members have often been slow to provide notification of domestic support levels. This makes the process of notification less useful as an indicator of the degree to which changes in policy have or have not benefited the trade system as a whole and exporting countries in particular. The notification of domestic support in the E.U. illustrates the value of a measure that reflects current policies and can therefore act as a basis for negotiation of further disciplines where these are necessary. The E.U. has made major changes in its Common Agricultural Policy (CAP) over the period since 1992 when the MacSharry reforms were implemented. Payments originally notified in the blue box (related to supply control) have over time been changed until in their present form they are unrelated to current production or price levels, and hence can satisfy the criteria for the green box. The E.U. has therefore much more latitude in trade talks to agree to reductions in the allowable trade-distorting support. This paper reproduced the E.U. notifications relating to 2003/04 and extends these with official statistics to the year 2006/07. It then projects forward the components of domestic support until the year 2013/14, based on forecasts of future production and estimates of policy parameters. The impact of a successful Doha Round is simulated, showing that the constraints envisaged in the WTO draft modalities document of May 19, 2008, would be binding by the year 2013, at about the time the next budget cycle in the E.U. starts. Without the Doha Round constraints, further reform might still happen for domestic reasons, but the framework provided by the WTO for domestic policy spending would be less relevant. In that case, much could hinge on the legitimacy of the Single Farm Payment system under the current rules governing the green box.